THE EFFECT OF EDUCATION LEVEL ON EMPLOYEE PERFORMANCE WITH TRAINING AS A MODERATING VARIABLE - Dian Wahyuningsih; Najmi Ismail; Bambang Suseno; Suratman; Rio Haribowo (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This research is a quantitative research with an explanatory approach (Lestari & Ghaby, 2018). The data used in this study are primary data that researchers obtained from Financial Services Authority employees spread throughout Indonesia as many as 5000 employees. The data were obtained from an online questionnaire and analyzed using the smart PLS 4.0 analysis tool with the following hypothesis. The result in this article show the Education Level variable can have a positive relationship direction and a significant influence on Employee Performance because it is positive and below the significance level of 0.05, namely 0.045. This means that the higher the education of an employee, the more it can influence employees to be more careful in understanding superiors' directions, working intelligently, and solving every problem that exists well, which ultimately improves Employee Performance.. In the next line, the researcher's hypothesis can also be proven if the Training variable can strengthen the influence of the Education Level variable on Employee Performance because the direction of the relationship is positive and the ebrad is below the significance level of 0.05, namely 0.021, which is more significant than direct testing of 0.05. Thus, the first and second hypotheses in this article can be accepted.